Comparison of Early Outcome of Off-pump and Conventional Coronary Artery Bypass Graft Surgery in Patients with Multivessel Coronary Artery Disease and Left Ventricular Dysfunction (Bangladesh Heart Journal, 2020)
Introduction: Left ventricular dysfunction is an important predictor of in-hospital mortality. Due to the theoretical and practical advantages to avoid the harmful effects of cardiopulmonary bypass (CPB), many cardiac surgeons are using Off-pump Coronary Artery Bypass (OPCAB)as an effective alternative to conventional CABG (CCAB) even in patients with reduced left ventricular (LV)ejection fraction. Objectives: This study performed in the National Institute of Cardiovascular Diseases (NICVD) evaluated the early outcomes of OPCAB in terms of mortality and major post-operative morbidities and compared them with that of CCAB in patients with multivessel coronary artery diseases and reduced left ventricular (LV) function.Methods: Total 120 patients with multivessel coronary artery disease with reduced left ventricular ejection fraction (d”50%)were allocated into two groups: a) 60 patients who underwent OPCAB and b) another 60 patients who underwent conventional CABG between January 2013 and December 2015. Pre-operative, peroperative and early post-operative variables were recorded, compiled and compared.Results: All risk factors and co-morbidities were homogenously distributed between the two groups. Majority of the patients had triple vessel disease. Nearly three-quarter (73.3%) of patients in OPCAB group and 80% in CCAB group received 3 grafts (p=0.470). The mean total operative time (268.5 ± 33.5vs. 296.3 ± 34.8minutes, p < 0.001), intubation times(8.6±0.3 vs. 12.3±0.5 hours, p